A noite também educa : compreensões e significados atribuídos por prostitutas à prática da prostituição - Sousa, Fabiana Rodrigues de (2012)
This research aimed to understand how prostitutes are educated in the practice of prostitution. This research is developed with the aim of transforming absences in presence, that is, seeking to understand the experiences of this social group that historically has been impelled to invisibility by the hegemonic order. For to think of education through experience and understand the prostitute in the movement of its existence, we use the theoretical contributions of popular education and phenomenology that strengthened the understanding that the process of educating themselves not only through effective intellection, but it is also true of perception and sensitivity. The phenomenon has been focused on the research is process of educating themselves on the night by women engaged in prostitution in nightclubs in São Carlos / SP. To grasp this phenomenon we used the following instruments: the field approach, coexistence, conversations with prostitutes, observation and field notes. The analysis of research is result of dialogue and coexistence with prostitutes and unveiled that through the availability, distrust and resistance, these women develop different educacional processes, such to facing adversity, weaving bonds of cooperation and solidarity, dealing with diversity, breaking gender conventions, make choices and implement actions to meet their needs, to get fancy, among others. There is much to learn with the prostitutes, but for this it is necessary to surround the phenomenon of prostitution and strip off of stereotypes. Only then can we realize that educating yourself in the night appears as praxis to transform reality, to reveal the prostitutes on the move in search to be more. Refuting the position of the victim these women create and experience new ways of being / living / work and reinvent the world, so the story.